Mechanical behavior of a Chinese traditional timber pagoda during construction. (1st October 2019) - Song, Xiaobin; Wu, Yajie; Li, Kai; Jin, Liangcheng; Chen, Feiming; Liu, Xiao; Dou, Xiaojing
Highlights: Construction monitoring was conducted on a seven-story Chinese traditional timber pagoda. Dynamic properties of the pagoda were measured in various construction stages. Simulation was conducted to assess the dynamic properties and safety of the pagoda. Abstract: Traditional timber structures in Southeast Asia and their craft techniques are of great historical and cultural value. This paper presents the monitoring results of a seven-story traditional timber pagoda in Shanghai during construction. The applied traditional craft techniques were recorded and briefed for better understanding of the structural behavior of the pagoda. Dynamic properties of the pagoda at various construction stages were measured via ambient vibration tests, and the influence of installation of various structural components on the frequencies of the pagoda in principal axes was identified. A three-dimensional numerical model was developed and verified based on the monitoring results, and was used to quantify the safety of the pagoda for which direct measuring is infeasible. It was found that the natural frequencies of the pagoda increased then decreased to the end of the construction due to the counteraction of the increase in both stiffness and mass. For example, the installation of the peripheral elements (columns, beams, dou-gong connections and roof components) of the ground to fifth stories increased the natural frequencies of the pagoda by up to 40%, while those of 6 th story decreased the frequencies by 37.3%. The timber frames assembled after the main structure increased the frequencies of the pagoda by no more than 7% due to the loose contact between the frame elements and the infill panels. It was also found that the internal forces induced to the mortise-tenon joints, dou-gong connections and timber frames were less than 6% of their loading resistances, implying a rather safe state of the pagoda. The generated knowledge can help deepen the understanding of Chinese traditional timber pagodas and be used as reference for renovation and retrofitting of existing Southeast Asian traditional timber structures.